2001
DOI: 10.1093/ije/30.3.616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking habit on medical care use and its costs: a prospective observation of National Health Insurance beneficiaries in Japan

Abstract: Smokers consume excess medical care. Among the population aged 45 years and over, about 4% of total medical costs were attributable to smoking. To pursue both better health and lower medical costs for the nation, a comprehensive programme to reduce tobacco use is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 14 publications
8
65
1
5
Order By: Relevance
“…As all of the analyses showed consistent trends (Supplementary Materials), we chose the commonly accepted threshold PY20 in the further analyses. (23) Multivariate analysis including EGFR, sex, and smoking status showed that only drug-sensitive EGFR mutations were significantly associated with longer OS and PFS (OS: hazard ratio = 0.48, 95% CI = 0.36 -0.63, P < 0.001) (PFS: hazard ratio = 0.29, 95% CI = 0.22-0.37, P < 0.001) ( Table 2). Next, we separated the impact of EGFR, sex, and smoking status on survival of patients treated with gefitinib to further understanding of these factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As all of the analyses showed consistent trends (Supplementary Materials), we chose the commonly accepted threshold PY20 in the further analyses. (23) Multivariate analysis including EGFR, sex, and smoking status showed that only drug-sensitive EGFR mutations were significantly associated with longer OS and PFS (OS: hazard ratio = 0.48, 95% CI = 0.36 -0.63, P < 0.001) (PFS: hazard ratio = 0.29, 95% CI = 0.22-0.37, P < 0.001) ( Table 2). Next, we separated the impact of EGFR, sex, and smoking status on survival of patients treated with gefitinib to further understanding of these factors.…”
Section: Resultsmentioning
confidence: 99%
“…Ever-smokers were classified into two categories based on the degree of cumulative smoking dose: 40 patients with light-to moderate-smoking status (0 < pack-years [PY] < 20), and 152 patients with heavy-smoking status (20 ≤ PY). (23) The details of the patient characteristics are shown in Table 1 Detection of EGFR mutations. The direct sequence with genomic DNA was used for all specimens analyzed in Okayama University Hospital and 66 specimens in National Cancer Center Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Em estudo conduzido por Izumi et al (2001) no Japão, observou-se que cerca de 92% dos indivíduos adultos utilizam, em média, 2 a 2,5 consultas médicas/mês. Na Califórnia, entre os participantes adultos, maiores de 40 anos de idade, em um estudo de intervenção, Lorig et al (2001) relatam cerca de 5,86 visitas ao médico ou a um serviço de emergência nos últimos 6 meses.…”
Section: Utilização De Serviços De Saúde Pelos Portadores De Problemaunclassified
“…If two or more articles were published on the same study, the most recent article was selected and the earlier article(s) not used. Eleven articles [19][20][21][22][23][24][25][26][27][28][29] were selected for calculating the ratio of mean medical expenditure between smokers and nonsmokers. We did not find many articles in which medical expenditures of female smokers were described.…”
Section: Articles and Information Collectedmentioning
confidence: 99%